KONSEP TEKNOLOGI PEMBELAJARAN : DEFINISI, SEJARAH DAN DESAIN PEMBELAJARAN - Arif Rahman Hakim; Isnan Rojibillah; Qiqi Yuliati Zakiyah; H. Supiana (An-Nahdlah: Jurnal Pendidikan Islam, 2025)
: Educational technology is a continuously evolving discipline alongside advances in information and communication technology. In education, it encompasses the planning, development, implementation, and evaluation of learning based on pedagogical principles. This article explores the concept of educational technology through three main aspects: definition, historical development, and instructional design models. The study employs a library research method with a descriptive qualitative approach. Data were obtained from academic sources such as textbooks, indexed journals, and education policy documents. The analysis is based on key theories from experts such as Seels & Richey, Reiser, and instructional design models including ADDIE, Dick & Carey, and Kemp. The findings show that educational technology has evolved from visual teaching aids into a complex and adaptive learning system. Its history reflects a transition from the pre-digital era to the age of networked learning and artificial intelligence. Instructional design serves as a crucial framework to ensure effective and learner-centered use of technology. The integration of learning theories—behaviorism, cognitivism, and constructivism strengthens its application. In conclusion, a comprehensive understanding of educational technology’s definition, history, and design is essential to address modern educational challenges and to create effective and sustainable learning processes in the digital era.